Comparison of Study Habits of Formal and Non formal students - Tahir Nawaz (IJLTP, 2025)
Study habits of students is an important aspect in the success of students. Students have their own learning needs and learning demands according to the geography and the local environment. Study habits include structured planning whether it is for students belonging to formal or non-formal streams. This study shed light on the comparison of study habits of formal and non-formal students. This paper aimed and compared study habits of formal and non-formal students. Quantitative research methods were used for data collection using questionnaires with a five-point Likert scale. For this purpose, 430 students were selected (350 from NFE and 80 from formal education). An independent sample t-test was used for analysis after data collection. The results obtained showed that the study habits of the formal students were better than the non-formal students in the Swat district.